1995
DOI: 10.1002/jlb.58.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of CD40 on fibroblasts induces CD54 (ICAM-1) and CD106 (VCAM-1) up-regulation and IL-6 production and proliferation

Abstract: CD40 was originally described as a functionally significant B cell surface molecule. However, CD40 is also expressed on monocytes, dendritic cells, epithelial cells, and basophils. We now report that synovial membrane (SM) or dermal fibroblasts also express cell surface CD40 in vitro. Fibroblast CD40 expression declines with increasing time in culture and recombinant interferon-gamma (rINF-gamma) induces fibroblast CD40 up-regulation. This effect of rINF-gamma is augmented by recombinant interleukin-1 alpha or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
154
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(170 citation statements)
references
References 28 publications
13
154
0
Order By: Relevance
“…The IL6 promoter contains NF-kB sites and is under dominant control by this transcription factor following TNF treatment (Libermann and Baltimore, 1990;Shimizu et al, 1990). CD40 has also been shown to mediate IL6 secretion (Clark & Shu, 1990;Hess et al, 1995;Yellin et al, 1995), however the molecular events leading to this e ect are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The IL6 promoter contains NF-kB sites and is under dominant control by this transcription factor following TNF treatment (Libermann and Baltimore, 1990;Shimizu et al, 1990). CD40 has also been shown to mediate IL6 secretion (Clark & Shu, 1990;Hess et al, 1995;Yellin et al, 1995), however the molecular events leading to this e ect are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested the functional expression of CD40 on T cells as well [5,6]. Stromal cells that express CD40 include thymic epithelia [7], vascular endothelium [8,9], keratinocytes [10,11], and fibroblasts [12]. Receptor expression is constitutive on B cells [13] and can be further up-regulated by interferon-␥ (IFN-␥) [1].…”
mentioning
confidence: 99%
“…CD40 ligand is expressed on activated T cells, and CD40 is expressed on FLS (37). Ligation of CD40 on FLS induces proliferation of FLS and upregulation of adhesion molecules such as intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 (23,38). Moreover, this interaction enhanced the production of cytokines, including IL-6 and vascular endothelial growth factor, by FLS (24,38).…”
Section: Discussionmentioning
confidence: 99%
“…Ligation of CD40 on FLS induces proliferation of FLS and upregulation of adhesion molecules such as intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 (23,38). Moreover, this interaction enhanced the production of cytokines, including IL-6 and vascular endothelial growth factor, by FLS (24,38). We therefore treated cocultures with neutralizing antibodies to CD40, which reduced the increments in chemokine production by 55-72%.…”
Section: Discussionmentioning
confidence: 99%